Dupont System: influential factors of profitability in companies in the manufacturing sector (Revista de Investigaciones Universidad del Quindío, 2022)
The general objective of this work has been to analyze, through the Dupont System, the factors influencing the profitability of large companies in the Colombian clay sector. Methodologically it is a quantitative, correlational and longitudinal study with panel data, to 26 large companies in the period 2016-2020, a multiple linear regression model is applied. As a result, the most influential variable of profitability is found to be net margin followed by asset turnover and financial leverage. The review of their sales strategies and costs is concluded as a focus of attention of the entrepreneurs.
Keywords: Dupont System; ROE; Net Margin; Asset Turnover; Leverage